2020
DOI: 10.1371/journal.pntd.0008153
|View full text |Cite
|
Sign up to set email alerts
|

Gender norms and mass deworming program access in Comé, Benin: A qualitative assessment of gender-associated opportunities and challenges to achieving high mass drug administration coverage

Abstract: The World Health Organization's Neglected Tropical Disease Roadmap has accelerated progress towards eliminating select neglected tropical diseases (NTDs). This momentum has catalyzed research to determine the feasibility of interrupting transmission of soil-transmitted helminths (STH) using community-wide mass drug administration (MDA). This study aims to identify potential gender-specific facilitators and barriers to accessing and participating in community-wide STH MDA, with the goal of ensuring programs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…This finding may be explained by other studies [ 24 , 36 , 37 ], which point to the geographic disparities in access to healthcare services in SSA. In analyzing a deworming program in Benin, Geyer et al found that the overwhelming rural context of Comé served as a barrier to effective mass drug administration delivery, as most resources were concentrated in the urban areas [ 14 ]. Similarly, it has also been suggested that long distances to healthcare centers in many regions, such as Borgou, Collines, and Atakora, may explain the low uptake of deworming medication [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may be explained by other studies [ 24 , 36 , 37 ], which point to the geographic disparities in access to healthcare services in SSA. In analyzing a deworming program in Benin, Geyer et al found that the overwhelming rural context of Comé served as a barrier to effective mass drug administration delivery, as most resources were concentrated in the urban areas [ 14 ]. Similarly, it has also been suggested that long distances to healthcare centers in many regions, such as Borgou, Collines, and Atakora, may explain the low uptake of deworming medication [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these efforts, the DeWorm3 Project was established to assess the feasibility of using mass drug administration to interrupt the transmission of soil-transmitted helminths (STHs), using study sites in Benin, along with India and Malawi [ 13 ]. The success of this intervention hinged on both high levels of treatment coverage and high levels of compliance [ 14 ]. While progress has been made through mass drug administration campaigns of donated medicines, these campaigns targeted and prioritized children in endemic regions over women of reproductive age [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A focus group in Benin, discussing gender-specific barriers to MDA programmes, noted that men sometimes do not see themselves at risk, and therefore have less demand for, for example, deworming, while women reported to seek increased involvement in MDA programmes. They concluded that door-to-door community-wide MDA programmes may improve general coverage, while at the same time "empower women by facilitating increased decision making" on behalf of their families (Geyer et al, 2020). However, the success of these programmes highly depends on the local gender roles, as in northern Nigeria drug distributors are sometimes unable to hand out PC when the man, as the head of the family, is not present in the house, meaning the entire family misses out on the preventive medication even in a door-to-door communitywide MDA programme (Burki, 2020).…”
Section: Gender and Sex Equity In Access To Healthcare In The Context Of Mass Drug Administration Programmesmentioning
confidence: 99%
“…Tailor programmes to gender-specific factors and include women in design of programmes: Understanding daily schedules of all genders will help when designing effective health programmes (Ozano et al, 2020). As previously mentioned, decentralised treatment and prevention programmes, such as door-to-door drug distribution, usually favour women more than a centralized approach does (Agbo et al, 2019;Geyer et al, 2020). This has to do with the household labour and responsibility that women have to their household, they are likely irreplaceable and often face consequences when needing to access healthcare for themselves.…”
mentioning
confidence: 99%
See 1 more Smart Citation